ChemInform Abstract: Chemoselective Intramolecular Wittig Reactions for the Synthesis of Oxazoles and Benzofurans. Issue 19 (May 2015) - Fan, Yu‐Shiou; Das, Utpal; Hsiao, Ming‐Yu; Liu, Meng‐Hsien; Lin, Wenwei
Abstract: By appropriate choice of reaction conditions or trapping reagents, the course of the reaction can be controlled towards chemoselective formation of either oxazoles or benzofurans.